Cardiac rehabilitation following an acute coronary syndrome: Trends in referral, predictors and mortality outcome in a multicenter national registry between years 2006–2013: Report from the Working Group on Cardiac Rehabilitation, the Israeli Heart Society. (January 2017) - Chernomordik, Fernando; Sabbag, Avi; Tzur, Boaz; Kopel, Eran; Goldkorn, Ronen; Matetzky, Shlomi; Goldenberg, Ilan; Shlomo, Nir; Klempfner, Robert
Background: Utilization of cardiac rehabilitation is suboptimal. The aim of the study was to assess referral trends over the past decade, to identify predictors for referral to a cardiac rehabilitation program, and to evaluate the association with one-year mortality in a large national registry of acute coronary syndrome patients. Design and methods: Data were extracted from the Acute Coronary Syndrome Israeli Survey national surveys between 2006–2013. A total of 6551 patients discharged with a diagnosis of acute coronary syndrome were included. Results: Referral to cardiac rehabilitation following an acute coronary syndrome increased from 38% in 2006 to 57% in 2013 ( p for trend < 0.001). Multivariate modeling identified the following independent predictors for non-referral: 2006 survey, older age, female sex, past stroke, heart or renal failure, prior myocardial infarction, minority group, and lack of in-hospital cardiac rehabilitation center (all p  < 0.01). Kaplan-Meier survival analyses showed one-year survival rates of 97% vs 92% in patients referred for cardiac rehabilitation as compared to those not referred (log-rank p  < 0.01). Multivariate analysis showed that referral for cardiac rehabilitation was associated with a 27% mortality risk reduction at one-year follow-up ( p  = 0.03). Consistently, a 32% lower one-year mortality risk was evident in a propensity score matched group of 3340 patients (95% confidence interval 0.48–0.95, p  = 0.02). Conclusions: Over the past decade there was a significant increase in cardiac rehabilitation referral following an acute coronary syndrome. However, cardiac rehabilitation is still under-utilized in important high-risk subsets of this population. Patients referred to cardiac rehabilitation have a lower adjusted mortality risk.